Important factors drive to brand image of superstore retail organization: an empirical study on shwapno - Azmat Ullah; Tanvir Morshad; Iftekhar Kaiser Shimul (Journal of Management and Science, 2022)
Super store retail organization is the popular in the world as well as Bangladesh. High and mid classes’ citizen in urban area are preferred for shopping any groceries products from superstore. Shwapno is the largest growing super chain shop in Bangladesh that provides all necessary commodities to the customers. This study is identified the factors which influence to the brand image and it drives to corporate image by providing perceived quality of products and services.The study has suggested top-level managers and authorities of Shwapno retail organization to consider these vital factors while enhancing brand image and leads to corporate image and aid to design the policies for retaining and satisfying their customers.